Changes in Medicago truncatula seed proteome along the rehydration–dehydration cycle highlight new players in the genotoxic stress response - Pagano, Andrea; Kunz, Laura; Dittmann, Antje; Araújo, Susana De Sousa; Macovei, Anca; Shridhar Gaonkar, Shraddha; Sincinelli, Federico; Wazeer, Hisham; Balestrazzi, Alma (Frontiers in Plant Science, 2023)
Introduction Several molecular aspects underlying the seed response to priming and the resulting vigor profile are still poorly understood. Mechanisms involved in genome maintenance deserve attention since the balance between stimulation of germination and DNA damage accumulation versus active repair is a key determinant for designing successful seed priming protocols. Methods Changes in the Medicago truncatula seed proteome were investigated in this study, using discovery mass spectrometry and label-free quantification, along the rehydration-dehydration cycle of a standard vigorization treatment (hydropriming plus dry-back), and during post-priming imbibition. Resuts and discussion From 2056 to 2190 proteins were detected in each pairwise comparison, among which six were differentially accumulated and 36 were detected only in one condition. The following proteins were selected for further investigation: MtDRP2B (DYNAMIN-RELATED PROTEIN), MtTRXm4 (THIOREDOXIN m4), and MtASPG1 (ASPARTIC PROTEASE IN GUARD CELL 1) showing changes in seeds under dehydration stress; MtITPA (INOSINE TRIPHOSPHATE PYROPHOSPHORYLASE), MtABA2 (ABSCISIC ACID DEFICIENT 2), MtRS2Z32 (SERINE/ARGININE-RICH SPLICING FACTOR RS2Z32), and MtAQR (RNA HELICASE AQUARIUS) that were differentially regulated during post-priming imbibition. Changes in the corresponding transcript levels were assessed by qRT-PCR. In animal cells, ITPA hydrolyses 2’-deoxyinosine triphosphate and other inosine nucleotides, preventing genotoxic damage. A proof of concept was performed by imbibing primed and control M. truncatula seeds in presence/absence of 20 mM 2’-deoxyinosine (dI). Results from comet assay highlighted the ability of primed seeds to cope with dI-induced genotoxic damage. The seed repair response was assessed by monitoring the expression profiles of MtAAG (ALKYL-ADENINE DNA GLYCOSILASE) and MtEndoV (ENDONUCLEASE V) genes that participate in the repair of the mismatched I:T pair in BER (base excision repair) and AER (alternative excision repair) pathways, respectively.